Peace Time : Cease-Fire Agreements and the Durability of Peace - Fortna, Virginia Page (Book collections on Project MUSE., 2004)
How to maintain peace in the aftermath of war is arguably one of the most important questions of the post-Cold War era, and one of the least explored issues in the study of war and peace. This book explains why some cease-fire fall apart quickly while others last for years.